Student Engagement in English for Nutrition: A Content-Based Instruction Implementation - Kartini Kartini; Sri Hariati Mustari; Riska Arnas; Muhammad Azwar Assiddiq (GLENS: Global English Insights Journal, 2026)
In the era of global health communication, Content-Based Instruction (CBI) has emerged as a crucial pedagogical approach in English for Specific Purposes (ESP). Although widely implemented in vocational education, its impact on student engagement among Nutrition students who require specialized English skills for international health literature and clinical counseling remains underexplored. This qualitative case study examines behavioral, emotional, and cognitive engagement during the implementation of CBI in an English for Nutrition course at Makassar State University. Data were collected through semi-structured interviews, classroom observations, and document analysis. Participants involved 30 undergraduate Nutrition students. The study utilized triangulation of data sources and methods, expert validation of the research instrument, and member checking to verify participant responses. Data were analyzed using reflective thematic analysis, involving transcription, coding, and categorization. Findings indicated that CBI significantly increased student engagement; behaviorally, students actively analyzed real-world clinical cases; emotionally, the relevance of the content reduced language anxiety; and cognitively, students demonstrated greater persistence in mastering complex terminology. However, varying levels of proficiency and limited medical vocabulary remained challenges. Overall, CBI effectively aligned language learning with professional development in healthcare.